Circular economy strategy and its application in the industrial sector - Ehinger, Lorenz Martin; Hönig, Vladimír, 1982-; Procházka, Petr; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
In the awe of an accelerating climate change, circular economy is becoming an increasing topic of interest both for public and private decision-makers as well as research. The goal of this thesis goal is to determine how biofuel producers can optimize reverse logistics in a circular economy to produce biofuels from used cooking oil using linear programming. The theoretical part provides a concise overview of circular economy, its definition, the legislative framework and national applications and progress in member states of the European Union. It further outlines the topic of biofuels, especially hydrotreated vegetable oils, their production and relevant policies and concludes with supply chain management in the circular economy. The practical part provides a framework within the model of linear programming to optimize reverse logistics The mathematical models within the framework serve as a decision-making aid to determine the cost-optimal supply, minimize distribution distance and maximize supply.
Vedoucí práce: Vladimír Hönig
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses